Implementation of Flipped Classroom Model on Distance Learning on Volta Cell Application Topics - Abdul Latip; Nursida Sutantri (Chemistry Education Department, 2021)
This study aims to analyze the implementation of the flipped classroom model in distance learning chemistry in the voltaic cell applications concept. This study used a descriptive method involving 1 teacher and 36 twelfth-grade students. The instrument used was an observation sheet to observe the flipped classroom model's learning process. The results showed that The implementation of the flipped classroom model in chemistry distance learning consists of 3 stages, namely before-class, during-class, and after-class, by combining synchronous and asynchronous activities. Students learn independently through videos with pre-learning questions as guidance in the before-class stage. In the during-class stage, synchronous learning is carried out through zoom meetings to discuss the concept of voltaic cell applications in specific contexts. At the after-class stage, learning is carried out asynchronously by providing a project to design an electrical energy generator that applies to the concept of a voltaic cell. The results showed that the flipped classroom model could be an alternative model for distance learning during the Covid 19 pandemic.